Physical Geology - Panchuk, Karla; Open Textbook Library (Open Textbook Library, 2019)
Physical Geology is a comprehensive introductory text on the physical aspects of geology, including rocks and minerals, plate tectonics, earthquakes, volcanoes, mass wasting, climate change, planetary geology and much more. It has a strong emphasis on examples from western Canada. It is adapted from "Physical Geology" written by Steven Earle for the BCcampus Open Textbook Program.
Chapter 1. Introduction to Geology -- Chapter 2. The Origin of Earth and the Solar System -- Chapter 3. Earth's Interior -- Chapter 4. Plate Tectonics -- Chapter 5. Minerals -- Chapter 6. The Rock Cycle -- Chapter 7. Igneous Rocks -- Chapter 8. Weathering, Sediment, and Soil -- Chapter 9. Sedimentary Rocks -- Chapter 10. Metamorphism and Metamorphic Rocks -- Chapter 11. Volcanism -- Chapter 12. Earthquakes -- Chapter 13. Geological Structures and Mountain Building -- Chapter 14. Streams and Floods -- Chapter 15. Mass Wasting -- Chapter 16. Earth-System Change -- Chapter 17. Glaciation -- Chapter 18. Geological Resources -- Chapter 19. Measuring Geological Time
In English.
Description based on online resource
Keywords: Earth Sciences -- Textbooks